Urban Agricultural Revolution in Japan With Verticulture Technology - Judijanto, Loso; Tan, Ethan; Lee, Ava (Techno Agriculturae Studium of Research, 2024)
Japan’s urban agricultural revolution with vertical culture technology emerged as a solution to overcome the limitations of agricultural land due to rapid urbanization. Vertical culture technology allows the cultivation of plants in urban environments by utilizing vertical spaces, thereby increasing food security and reducing environmental impact. This study aims to analyze the development and impact of the application of verticulture technology in major Japanese cities, as well as identify the factors that support its success. The research method used is qualitative descriptive with data collection through in-depth interviews, direct observation, and secondary data analysis from government reports and scientific publications. The results show that the number of vertical culture installations in Japan has increased significantly in the last five years, supported by government policies and local community initiatives. In addition to increasing food production in urban areas, this technology also helps create green spaces and improve environmental quality in densely populated areas. The conclusion of this study is that verticulture can be a sustainable solution for urban food security, but further research is needed to evaluate the long-term impact on the environment and energy efficiency.